Administration of IL-1β to the 4th ventricle causes anorexia that is blocked by agouti-related peptide and that coincides with activation of tyrosine-hydroxylase neurons in the nucleus of the solitary tract - DeBoer, Mark D. (2008)
Inflammation-associated cachexia is associated with multiple chronic diseases and involves activation of appetite regulating centers in the arcuate nucleus of the hypothalamus (ARH). The nucleus of the solitary tract (NTS) in the brainstem has also been implicated as an important nucleus involved in appetite regulation. We set out to determine whether the NTS may be involved in inflammation-associated anorexia by injecting IL-1β into the 4th ventricle and assessing food intake and NTS neuronal activation. Injection of IL-1β produced a decrease in food intake at 3 and 12 h after injection which was ameliorated at the 12 h time point by a sub-threshold dose of agouti-related peptide (AgRP). Investigation into neuron types in the NTS revealed that IL-1β injection was associated with an increase in c-Fos activity in NTS neurons expressing tyrosine hydroxylase (TH). Additionally, injection of IL-1β into the 4th ventricle did not produce c-Fos activation of neurons expressing pro-opiomelanocortin (POMC) in the ARH, cells known to be involved in producing anorexia in response to systemic inflammation. Double-label in situ hybridization revealed that TH neurons did not express IL-1 receptor I (IL1-RI) transcript, demonstrating that c-Fos activation of TH neurons in this setting was not via direct stimulation of IL-1β on TH neurons themselves. We conclude that IL-1β injection into the 4th ventricle produces anorexia and is accompanied by an increase in activation in TH neurons in the NTS. This provides evidence that the brainstem may be an important mediator of anorexia in the setting of inflammation.